2011
DOI: 10.1108/09578231111146470
|View full text |Cite
|
Sign up to set email alerts
|

Making the right choices: ethical judgments among educational leaders

Abstract: Purpose-Scholars have adopted a multiple ethical paradigms approach in an attempt to better understand the bases upon which everyday ethical dilemmas are resolved by educational leaders. The aim of this study is to examine the ethical considerations in ethical judgments of aspiring principals. Design/methodology/approach-To examine the ethical considerations involved in school leadership decision making, a specially designed ethical perspective instrument was developed that draws on the multiple ethical paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 44 publications
3
73
0
2
Order By: Relevance
“…Quick and Normore (2004) noted some leaders may naturally and unconsciously prefer one ethic to another. Eyal, Berkovich, and Schwartz (2011) found that 52 participants in principal training programs in Israel were more likely to use the ethic of critique in their decision making. Leaders can correct a predominant reliance on one ethic by proactively seeking a balance (Quick & Normore, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Quick and Normore (2004) noted some leaders may naturally and unconsciously prefer one ethic to another. Eyal, Berkovich, and Schwartz (2011) found that 52 participants in principal training programs in Israel were more likely to use the ethic of critique in their decision making. Leaders can correct a predominant reliance on one ethic by proactively seeking a balance (Quick & Normore, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In our prior work, we developed an Ethical Perspectives Instrument (EPI) that explores ethical judgment indirectly, based on choosing between multiple ethical paradigms (Eyal et al, 2011; EPI form and SPSS syntaxes are available at www.izhakber.com/EPI). This instrument was used to explore the effects of an ethics academic course based on extended multiple ethical paradigms.…”
Section: Empirical Research On the Effectiveness Of Ethics Education mentioning
confidence: 99%
“…According to writers (see Eyal et al, 2011;Knapp and Feldman, 2012;Mintrop, 2012;Strike, 2007), it is important that leaders are able to find a balance in how they act upon competing priorities in schools. Yet what this balance looks like in practice is not commonly discussed nor likely to be the same in every context.…”
Section: Jea 532mentioning
confidence: 99%